164. Antimicrobial Susceptibility of Urogenital and Extragenital Neisseria gonorrhoeae Isolates Among Men Who Have Sex with Men – SURRG and eGISP, 2018–2019. (4th December 2021) - Quilter, Laura; Cyr, Sancta St; Hong, Jaeyoung; Asbel, Lenore; Bautista, Ilene; Carter, Bonnie; Casimir, Yanick; Denny, Michael; Ervin, Melissa; Gomez, Raquel; Harvey, Alesia; Holderman, Justin; et al.
Abstract: Background: Extragenital gonococcal infections are common among men who have sex with men (MSM); however, data comparing antimicrobial susceptibilities of urogenital and extragenital Neisseria gonorrhoeae isolates are limited. We investigated differences in gonococcal antimicrobial susceptibility by anatomic site among cisgender MSM using specimens collected through CDC's enhanced Gonococcal Isolate Surveillance Project (eGISP) and Strengthening the U.S. Response to Resistant Gonorrhea (SURRG). Methods: During January 1, 2018–December 31, 2019, 12 eGISP and 8 SURRG sites collected urogenital, pharyngeal, and rectal isolates from cisgender MSM in STD clinics. Gonococcal isolates were sent to regional laboratories for antimicrobial susceptibility testing by agar dilution. To account for correlated observations, linear mixed-effects models were used to calculate geometric mean minimum inhibitory concentrations (MICs) and mixed-effects logistic regression models were used to calculate the proportion of isolates with elevated or resistant MICs; comparisons were made across anatomic sites. Results: Participating clinics collected 3, 974 urethral, 1, 553 rectal, and 1, 049 pharyngeal isolates from 5, 456 unique cisgender MSM. There were no significant differences in the geometric mean MICs for azithromycin, ciprofloxacin, penicillin, and tetracycline by anatomic site. For cefixime and ceftriaxone, geometric mean MICs for pharyngeal isolates were higher compared to anogenital isolates (p< 0.05). The proportion of isolates with elevated ceftriaxone MICs (≥ 0.125 µg/ml) at the pharynx (0.67%) was higher than at rectal (0.13%) and urethral (0.18%) sites (p< 0.05). Conclusion: Based on data collected from multi-jurisdictional sentinel surveillance projects, antimicrobial susceptibility patterns of N. gonorrhoeae isolates may differ among MSM at extragenital sites, particularly at the pharynx. Continued investigation into gonococcal susceptibility patterns by anatomic site may be an important strategy to monitor and detect the emergence of antimicrobial resistant gonorrhea over time. Disclosures: Olusegun O. Soge, PhD, Hologic Inc. (Grant/Research Support)SpeeDx Inc. (Grant/Research Support) Stephanie N. Taylor, MD, GARDP - GC Antibiotic Development (Scientific Research Study Investigator, To my institution.)GlaxoSmithKline (Grant/Research Support, Funds to my institution.)